MEMBENTUK KARAKTER ANAK DIDIK MELALUI PASRAMAN (SEBUAH SOLUSI SISTEM PENDIDIKAN NASIONAL) - Sentana Putra, Kadek Dwi (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Education is a very important aspect in the life of each individual, because through education human will get knowledge that can be used in their life. Education can be obtained in various ways, one of them is through the school, where the character of each child is expected to be formed since an early childhood. However, currently there are phenomena which indicate the presence of moral degradation exhibited by school-age children, such as the number of student fights and deeds other improperly. Seeing this phenomenon, arises the question "What's wrong with the education system these days?? In Hinduism known the education is done through pasraman system (ashram), which is a student came and stay in the dorm of a teacher for a long time to get the desired knowledge. Referring to this system, arise author wishes to reappoint as a discourse to be used as a discussion whether the pasraman system can be developed as a method of formal education, in order to create Indonesian beings who not only have a high intellectual capability, but beings character as well.   The Pasraman education concept is an educational concept embodied in the Hindu Vedic scriptures, which describes the relationship between the teachers who are familiar with the student. The Pasraman purpose is: (1) To provide to the student's basic ability to develop individuals who have Sraddha and bhakti to the God, and (2) to nurture students to have the experience, knowledge, and skills that can be developed in their life.  Viewed from the goal, either education based on pesraman system and national education systems have in common is equally aims to develop the potential of the child to have the spiritual strength of religious, self-control, personality, intelligence, noble character and skills necessary for himself, society, nation and state. So both of the education system can be said to be in line. Thus education based on pesraman can be offered as one solution to solve the problems faced by the National Education System, especially in the formation of students' character In order pasraman education can be developed into an education system that is universal, it need the intervention of Dirjen Bimas Hindu contributed to ask and convince government authorities that pesraman education system is a solution for achieving National Education goals, so that education can be recognized in pasraman as one of the methods of formal education in Indonesia, not only as a religious-oriented education.